MENENTUKAN STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN CCTV HIKVISION SURABAYA DI TENGAH PANDEMI COVID 19 - Nova Retnowati; Enny Istanti (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
The Covid-19 pandemic has forced everyone to do all activities at home, therefore the telecommunications business has become a business that is quite profitable and promising in accordance with the online WFH system in Indonesia. Based on this situation, the research was conducted to determine the marketing strategy in increasing sales of Hikvision CCTV in Surabaya. This research was conducted with the aim of knowing and analyzing marketing strategies in increasing Hikvision CCTV sales in Surabaya in the midst of the Covid19 pandemic. The results of the SWOT analysis can be used as a basis for companies to determine marketing strategies to increase sales volume. The method used in this research is descriptive research with a SWOT analysis approach. The techniques used in data collection are basic observations and interviews and are related to marketing strategies including product, price, place, and promotion strategies that are used to identify strengths, weaknesses, opportunities and threats with SWOT analysis. The results of the SWOT analysis show that Hikvision CCTV is in quadrant II, which means that despite facing various threats, Hikvision CCTV still has internal strength. The strategy that should be implemented is to use strengths that take advantage of long-term opportunities by means of a diversification strategy (product or market).